Recent Advances in the Field of Xenon(II) Compounds with Polymeric Fluoridoanions - Radan, Kristian (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2022)
The synthesis of the first noble-gas compound, "XePtF6", was reported 60 years ago and has been followed by several unsuccessful attempts at structural characterisation over the past decades. It was suggested that the elusiveness of "XePtF6" might be attributed to the polymeric nature of its anion. Since polyfluoridometalate anions were also found to arise from the interaction of XeF2 with weaker Lewis acids, such as certain metal tetrafluorides, a series of analogous XeF2–MF4 (M = Cr, Mn, Sn, Ti) systems were systematically investigated, where it was shown that despite their relatively simple formulation aXeF2·bMF4, the isolated products exhibit a very rich structural chemistry featuring a variety of anions with different dimensionality. In this study, excess XeF2 was reacted with SnF4 in anhydrous HF. The products were characterized with low-temperature single-crystal X-ray diffraction and Raman spectroscopy. Two Xe2F3+ compounds with novel 2D polyfluoridostannate anions were isolated: [Xe2F3][Sn4F17]·XeF2·HF and [Xe2F3]3[Sn10F43]·2XeF2. Moreover, XeF2 was heated with TiF4 at 135°C. Upon cooling to room temperature, crystals of [XeF][Ti4F17] were obtained. This compound with the novel 2D [Ti4F17]− anion represents a new isomer of XeF2·4TiF4, since previously only [Xe2F3][Ti8F33] was known.